GANGGUAN KULIT PEMULUNG DI TPA KENEP DITINJAU DARI ASPEK KESELAMATAN DAN KESEHATAN KERJA - Karunia Friska Pratama; Corie Indria Prasasti (Universitas Airlangga, 2017)
scavenger is one of job that have a risk for the health or work safety cause usually interact with the garbage as a source of disease factor and can be a good place for disease vector development. The purpose of this study is to know the skin disease that happens at scavenger from occupational safety and health aspect. The population are 43 people , and the sample amount is 33 people which found from simple random sampling technique. The result showed that most of damage excerpter are women with work period from more than 4 years, work in less than 8 hours a day. From 33 people, 27 people have skin disease, with 7 people got tinea unguium diagnosis.. Another kind of skin disease that found at scavenger are, tinea korporis, tinea falvalis,tinea versikolor, candidiasis, karbonkel, folikulitis, dan miliria rubra that cause of mush,parasite, and high perspiration activity. Skin disease can happens cause of the more of cloth using and high temperature climate and less of personal hygiene from damage scavenger work pattern.